Pemanfaatan Aplikasi Canva Sebagai Media Pembelajaran Matematika Materi Bangun Datar Kelas VII Di SMP Negeri 1 Citeureup - Nissa Nur Fadillah; Astri Astuti; Alfiatussyifa Alfiatussyifa (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to determine the feasibility, practicality and effectiveness of using the Canva Application as a Mathematics Learning Media for Class VII Flat Building Material at SMP Negeri 1 Citeureup.This research adopts the ADDIE model stages (analyze, design, develop, implement, and evaluate). The analyze stage includes initial analysis, student analysis, concept analysis and formulating learning objectives. The design stage includes preparing learning media in the form of selecting appropriate media and designing learning content. The development stage includes the development of data collection instruments. The data collection instrument in this research was interviews with the teachers concerned. The implementation stage includes implementing the use of the Canva application. The evaluation stage includes the form of evaluation carried out at each ADDIE stage. The data analysis technique used is the validity coefficient by Aiken's V. The research results show that the learning media that has been developed is in the very good category and can be used in the learning process.